Od Žižeka prema postsocijalizmu - Jukić, Tatjana (2013)
Taking up Žižek’s position on Marxism in The Fragile Absolute, I argue that Žižek traces the metonymic logic of the international which dehomogenizes his take on universalism, as well as the Cartesian logic of his engagement with Lacan’s psychoanalysis. What surfaces instead is a critical imaginary where Žižek’s Lacanian script registers a shift towards configurations formative to the work of Gilles Deleuze, specifically towards Deleuze’s view of masochism. This in turn is where a position emerges for the analysis of how the communist revolution, with its Marxist inflection, deregulates socialism but informs postsocialism, with the socialist Yugoslavia as a case in point.
Projekt MZOS
HRV